Hamdani Bakran Adz-Dzakieyâ€™s Sufism Psychotherapy as Part of the Medication for Muslim Mental Illness - Nofiya Dwi Pangesti (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
This research is aimed to describe and analyze the concept of sufism psychotherapy as part of the medication for muslim mental illness according to Hamdani Bakran Adz-Dzakiey. The type of this research is library research. The Data Collection Method is the documentation and interview. The Data Analysis Technique uses an interactive analysis model developed by Miles and Huberman, which includes: data reduction, display data, and conclution drawings. The results of this research are: First, Hamdani Bakran Adz-Dzakiey’s Sufism Psychotherapy is derived from empirical and prophetic-based experience and used methods of tasawuf (takhalli, tahalli, and tajalli). Second, Sufism psychotherapy function are for self-purification, self-identification, self- prevention, self-education, self-development, self-prediction, self-control, and self-understanding.